Honey as a wound dressing on superficial partial-thickness burn injury in a resource-limited setting: An EBCR at Ende General Hospital - Wiguna, Komang Alit Artha; Siregar, Sun Perkuseg (PT. Mega Science Indonesia, 2024)
This study aimed to compare the efficacy of honey and conventional SSD cream in accelerating burn wound healing, specifically in resource-limited healthcare settings. A comprehensive literature search was conducted using PubMed and Cochrane databases. Following systematic screening of titles and abstracts based on predetermined inclusion and exclusion criteria, six articles were selected for analysis, comprising four systematic reviews, one randomized controlled trial (RCT), and one cross-sectional study. The methodological quality of the selected studies was critically appraised using validated tools from the Centre for Evidence-Based Medicine, University of Oxford. The analysis included six studies: four systematic reviews, one randomized controlled trial (RCT), and one cross-sectional study. six studies: four systematic reviews, one randomized controlled trial (RCT), and one cross-sectional study. Quality assessment indicated that the systematic reviews and cross-sectional study demonstrated robust methodological quality. These high-quality studies consistently reported significant reductions in burn wound healing time when honey dressings were utilized. However, the included RCT failed to report effect measurements, limiting the interpretation and clinical significance of its findings. Honey has a faster healing effect on superficial thickness burns than SSD cream and is affordable. Therefore, honey can be used as an alternative wound dressing in areas with limited facilities.